Treatment evaluation for vegetative propagation of tripeperro (Philodendron longirrhizum M. M. Mora & Croat) handcrafts-used specie in Quindio department (Revista de Investigaciones Universidad del Quindío, 2011)
The “tripeperro” (Philodendron longirrhizum) is a widely used species for the production of handicrafts in the Department of Quindío. That is why vegetative propagation was evaluated as an alternative to minimize the negative impact of their exploitation. In the farm called “La Aldana”, property of the University of Quindio, stem cuttings were planted in nine treatments consisting of the addition of organic fertilizer (vermicompost) and chemical fertilizer (NPK 25-5-10) with or without the direct application of a rooting to base of naphthalene acetic acid (NAA). The treatments were conducted under randomized block design, each with 10 repetitions, for a total of 90 stem cuttings evaluated, carried out fortnightly monitoring for nine months. It was established that chemical fertilizer treatments and control, which did not apply any type of substance, produced better results in the development of leaf buds, the average number of leaves and the average width of the leaf blade. From the results, it is suggested that the propagation of Philodendron longirrhizum by a vegetative way is viable and low cost to the farmer since it can be planted in soil without adding any fertilizer, so it can be said that this strategy may contribute to the conservation of the species and ensure continuity in the baskets and handicrafts business in the department of Quindío.
Keywords: stem cuttings; tripeperro; vegetative propagation